PROCUREMENT OF LAND IN LEGAL SOCIOLOGICAL PERSPECTIVE - Roestamy, Martin (Magister Ilmu Hukum Sekolah Pascasarjana Unida, 2017)
If all stakeholders of land provision adhere to the principles governed by the Constitution and the State Controlling Right, then the issue of the regulation of land will not be a national dilemma inheriting a prolonged conflict and not less as a result of the loss of life. Land is something sacred (magical) for people who have historical and spiritual value is not just a matter of investment and business commodities that have been going on, but the land is the right of the nation that has the value of the struggle that becomes the object of the interests of all parties, the people, government, and speculators. This research is expected to be an input to stakeholders to support the birth of Land Bank as an institution in charge of providing land for public interest. The research was conducted by using Sociological Juridical Method combined with Normative Juridical with a Qualitative Approach. It concerns the problem of access to the rule of law which cannot run properly, and legal culture is still low so that with the sociological and juridical approach. Those can be found the nature of the primary cause problematic of land supply in Indonesia, especially for the public interest and more specifically for the benefit of providing housing for low-income people.Keywords : Procurement of Land, Legal Culture, State Right Controlling, Land Bank